MORAL AND PURPOSEFUL COMPONENT OF LEGAL COMPETENCE OF VOCATIONAL TEACHERS OF CONSTRUCTION INDUSTRY VOCATIONAL EDUCATION INSTITUTIONS (Innovative professional education, 2025)
The article analyses the moral and purposeful component of the legal competence of vocational teachers of vocational education institutions in the construction industry, outlines its content characteristics and mechanisms of formation. The significance of moral and legal guidelines in the professional training of students is determined, the role of teachers in the formation of legal awareness of future specialists is emphasised. The results of an empirical study are presented, which show a significant level of awareness of teachers of the need for legal education and the impact of moral standards on students as future specialists in the construction industry
Keywords: vocational teacher educator, legal competence, moral and purposeful component, survey